Relative importance of clinical outcomes and safety risks of antiseizure medication monotherapy for patients and physicians: Discrete choice experiment eliciting preferences in real‐world study "VOTE". Issue 2 (17th December 2021) - Rosenow, Felix; Winter, Yaroslav; Leunikava, Iryna; Brunnert, Marcus; Joeres, Lars; Sutphin, Jessie; Boeri, Marco; Smith, Jasmine; Villani, Flavio; Brandt, Christian
Abstract: Objective: This study was undertaken to elicit patients' preferences for attributes characterizing antiseizure medication (ASM) monotherapy options before treatment consultation, and to explore the trade‐offs patients consider between treatment efficacy and risks of side effects. Further objectives were to explore how treatment consultation may affect patient preferences, to elicit physicians' preferences in selecting treatment, and to compare patient and physician preferences for treatment. Methods: This prospective, observational study (EP0076; VOTE) included adults with focal seizures requiring a change in their ASM monotherapy. Patients completed a discrete choice experiment (DCE) survey before and after treatment consultation. Physicians completed a similar survey after the consultation. The DCE comprised 12 choices between two hypothetical treatments defined by seven attributes. The conditional relative importance of each attribute was calculated. Results: Three hundred ten patients (mean [SD] age = 46.8 [18.3] years, 52.3% female) were enrolled from eight European countries, of whom 305 completed the survey before consultation and 273 completed the survey before and after consultation. Overall, this preference study in patients who intended to receive a new ASM monotherapy suggests that patient preferences were ordered as expected, with better outcomes being preferred to worse outcomes; patients preferred a higher chance of seizure freedom, lower risk of developing clinical depression, and fewer severe adverse events; avoiding moderate‐to‐severe "trouble thinking clearly" was more important than avoiding any other side effect. There were qualitative differences in what patients and physicians considered to be the most important aspects of treatment for patients; compared with patients, physicians had a qualitatively stronger preference for greater chance of seizure freedom and avoiding personality changes. Patients' preference weights were qualitatively similar before and after treatment consultation. Significance: For patients, seizure freedom and avoiding trouble thinking clearly were the most important treatment attributes. Physicians and patients may differ in the emphasis they place on specific attributes.